PSYCHOLOGICAL CONFLICT OF DORIAN GRAY IN THE NOVEL ENTITLED THE PICTURE OF DORIAN GRAY BY OSCAR WILDE - Naratri, Aisya Rizka (LANTERN (Journal on English Language, Culture and Literature), 2016)
In this paper, the writer would like to analyze a novel entitled The Picture of Dorian Gray by Oscar Wilde. The purpose of this writing is to analyze the psychological conflict of the main character. The writer uses psychoanalysis theory to analyze the psychological conflict of the main character in the novel and use library research. In this theory, the writer will discover the changes behavior of Dorian Gray. The main themes in this novel are youth, beauty and homosexuality; it becomes the reason why the writer entitles “Psychological Conflict Dorian Gray in The Novel Entitled “The Picture of Dorian Gray” by Oscar Wilde”.